Sociomental Characteristics of Modern Youth (According to the Results of Study) - V Karpenko, Ekaterina (International Journal of Psychosocial Rehabilitation, 2020)
The article informs about a complex study that has enabled the obtaining and comparing of sociological, socio-psychological, sociometric, and sociomental characteristics of respondents. The goal of the article is to describe the results of this study aimed at searching for the methods and approaches enabling the development of such a level of communicative skills that would enable a person to arrange multi-level structures of communicative-cognitive programs in his conscious mind that are adequate to those programs that are implicit in the perceived texts, to identify the primary, the secondary, the tertiary, etc. in them, and, as a result, to understand the author’s motives and goals (meaning). The study has involved semiosociopsychological methods enabling the differentiation of the audience by communicative skills, including the method of intentional (motivational-target) analysis of communication processes within a framework of semiosociopsychological paradigm. Special procedures enable, first, the arrangement of motivational-target structures of the works named by a respondent and, second, motivational-target structures for interpreting these very works; the comparison of the obtained structures gives the idea of the degree of understanding the author’s intentionality and the peculiarity of “reflecting” main semantic dominants in the consciousness. In the end, we succeeded in comparing the parameters of socio-mental characteristics of the group of respondents under study with socio-mental peculiarities of related socio-demographic groups starting from the 1970s. The results of the study are associated with one of the conclusions that the skills of adequate perception are more developed in the students of humanitarian universities than in the students of technical universities; the level of development of communicative skills hardly changes throughout the time, in spite of the development of engineering, ways to obtain information, new and advanced technologies, and other achievements associated with the representations of progress. Thus, the high level of communicative skills associated with human ability to orient adequately in the communicative processes should become one of the obligatory characteristics of people making socially significant decisions, bringing children and youth up, and educating them.